2018
DOI: 10.1016/j.bbmt.2018.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell (MSC)-Derived Combination of CXCL5 and Anti-CCL24 Is Synergistic and Superior to MSC and Cyclosporine for the Treatment of Graft-versus-Host Disease

Abstract: The immunosuppressive properties of mesenchymal stromal cells (MSCs) have been clinically proven to be effective in treating graft-versus-host disease (GVHD). However, MSC therapy is limited by the need for laborious and expensive manufacturing processes that are fraught with batch-to-batch variability. Substitution of MSC therapy with key MSC-mediated immunomodulatory factors could be an option for GVHD treatment. Using a simulated in vitro model of the immunosuppressive effects of MSC on allogeneic graft rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…and Th17, CTLs and NK cells [46][47][48][49]. Similarly, VEGFC/VEGFR3 signaling closely connected with LINC01116 and LINC00460 were mainly expressed on immune cells including macrophages and NK cells, and might also disturb ICB e cacy via affecting dendritic cells and CD8 T cells [50][51][52], or inducing the naïve T cells via CCL21 [53].…”
Section: Discussionmentioning
confidence: 98%
“…and Th17, CTLs and NK cells [46][47][48][49]. Similarly, VEGFC/VEGFR3 signaling closely connected with LINC01116 and LINC00460 were mainly expressed on immune cells including macrophages and NK cells, and might also disturb ICB e cacy via affecting dendritic cells and CD8 T cells [50][51][52], or inducing the naïve T cells via CCL21 [53].…”
Section: Discussionmentioning
confidence: 98%
“…Besides, an ocean of data indicated that aGVHD could be alleviated with up-regulation of CXCL5 and anti-CCL24 antibody [90]. The mechanism is illustrated in the Fig.…”
Section: Application In Acute Graft-versus-host Disease (Agvhd)mentioning
confidence: 93%
“…Additional MSC therapy after an initial induction therapy can further improve the outcomes of patients. Another study assessed the feasibility of an MSC-derived 2-factor combination (2FC) of CXCL5 and anti-CCL24 in place of MSCs in the treatment of GvHD 48 . In this study, GvHD mouse models were produced via the tail vein injection of human PB mononuclear cells (PBMCs) into NSG mice, followed by Cesium 1 , 37 irradiation in mice 3 to 4h before PBMC transplantation 48 .…”
Section: Mesenchymal Stromal Cells (Msc) (Table 3)mentioning
confidence: 99%